Laparoscopic Cholecystectomy: Complication and Conversion Rate - Malla, B R; Shrestha, R K M (Kathmandu University Medical Journal, 2012)
Background Laparoscopic cholecystectomy has become standard method for treating gallstone. However, different centres have reported different complications and conversion rate. The objective of this study was to evaluate complications and conversion of laparoscopic cholecystectomy into open cholecystectomy in Dhulikhel Hospital, Kathmandu University, Nepal. Methods Files of all patients who had laparoscopic cholecystectomy from January 2005 to December 2009 were reviewed. Out of 119 laparoscopic cholecystectomy cases, 102 were included in the study as complete information was lacking in the rest. Results Out of 102 cases, 80 were female. Symptomatic cholelithiasis were 76.47%. The mean hospital stay was 2.48 days. Postoperative complications occured in 5.88% patients. Conversion rate to open cholecystectomy was 3.92%. Conclusions Laparoscopic cholecystectomy is a reliable and safe surgery. With growing experience in laparoscopic technique, it is possible to bring complications and conversion rate to minimum. However, there will be no significant improvements once learning curve is reached. Rather, the nature of biliary injury may become more severe. http://dx.doi.org/10.3126/kumj.v8i4.6232 Kathmandu Univ Med J 2010;8(4):367-9